(untitled) (Journal of Patan Academy of Health Sciences, 2020)
Introduction: An abbreviation is a shortened form of word or phrase commonly used in medical practice for convenience. Misinterpretation of abbreviations can lead to confusion and medical errors. Studies have shown the use of abbreviations early as the first year in medical school. Method: A cross-sectional questionnaire-based survey among undergraduate clinical year medical students in the tertiary care center of Kathmandu Valley was performed from December 2017 to April 2018. Result: A total of 97 participants. The prevalence of abbreviation use was 95%. Senior students correctly interpreted both standard and non-standard abbreviations. The majority of students learned to use abbreviations from the medical officer’s note. Conclusion: Students consider abbreviations are acceptable despite having difficulties in interpretation. Hospitals or concerned departments should regulate the use of standard abbreviations.